Conflation of satellite altimetry and tide gauge records at coast - Iz H. Bâki; Shum C. K.; Yang T. Y. (Journal of Geodetic Science, 2020)
This study demonstrates that absolute (geocentric) and relative sea level trends, sea level acceleration, low frequency sea level variations and linear trends in vertical crustal movements experienced at a tide gauge station can be estimated simultaneously using conflated satellite altimetry and tide gauge measurements without the aid of GPS measurements. The formulation is the first of its kind in sea level studies and its effectiveness is exemplified using tide gauge, and satellite altimetry measurements carried out in the vicinity of a tide gauge station.